Predictors of severe intraventricular hemorrhage in preterm infants under 29-weeks gestation. (17th January 2021) - Siddappa, Ashajyothi M.; Quiggle, Gabrielle M.; Lock, Eric; Rao, Raghavendra B.
Abstract: Purpose: Preterm infants <29 weeks of gestation are at risk for severe intraventricular hemorrhage (IVH). Lower gestational age, birth weight, severe illness, as indexed by higher Score for Neonatal Acute Physiology - Perinatal Extension II (SNAPPE-II) are associated with severe IVH. The role of coagulation abnormalities on the first day after birth in severe IVH remains controversial. The present study investigated factors that predict the risk of severe IVH, including SNAPPE-II at 12 h and coagulation parameters on the first day after birth. Materials and methods: A retrospective chart review of infants < 29 weeks of gestation from January 2008 to December 2013 was performed. Prenatal and postnatal characteristics, SNAPPE-II at 12 h, coagulation parameters [prothrombin time (PT), INR, partial thromboplastin time (aPTT), thrombin time (TT), and fibrinogen] on the first day and cranial ultrasound examination records were collected. The association between clinical and laboratory variables and severe IVH was determined. A joint predictive model for the risk of severe IVH (grades 3 and 4) versus no-mild IVH (grades 0, 1, and 2) was developed using multiple regression analysis. Results: Preterm infants of gestational age < 29 weeks were included ( n = 101). Fifteen (15%) infants had severe IVH. Lower gestational age ( p = .006), birth weight ( p = .008), African American race ( p = .031) and higher SNAPPE-II at 12 h ( p = .001) were associated with severe IVH. Infants with severe IVH had longer PT ( p = .004), higher INR ( p = .004) and lower platelet count ( p = .034) than those with no-mild IVH. Stepwise logistic regression showed that only SNAPPE-II at 12 h was an independent predictor of severe IVH. For each unit increase in SNAPPE-II, the log odds of severe IVH increased by 0.045 (95% CI: [0.017, 0.073]; p = .002). A threshold of 55 on the SNAPPE-II yielded a sensitivity of 60% (9/15), a specificity of 91% (78/86), a positive predictive value (PPV) of 53% (9/17) and a negative predictive value (NPV) of 93% (78/84). All other demographic and clinical variables and coagulation abnormalities had an insignificant coefficient ( p > .05) when included in a bivariate logistic model with SNAPPE-II. Conclusion: SNAPPE-II at 12 h after birth is an independent predictor of severe IVH in preterm infants with gestational age < 29 weeks.